Grammatical Error Analysis in Descriptive Writing of Accounting Students at Politeknik Harapan Bersama Tegal - Syaefani Arif Romadhon -; M. Taufik Qurohman; Muchamad Sobri Sungkar (ELT-Lectura, 2020)
Most students have difficulty in learning English especially for Writing material, because in addition to the problem vocabulary there is also a lack of student’s understanding of Grammar. It takes a while to work on Writing because it should consider the aspects of Vocabulary and Grammar. This research was conducted to find some Grammar errors which commonly done by students of Accounting study Program at Politeknik Harapan Bersama Tegal. So the purpose of this research is to analyze student Grammar mistakes in particular in descriptive text. This research uses qualitative descriptive methods as a method of research. Data presented in the form of descriptive analysis. From the results of the study showed that students make mistakes on the Verb Agreement 7.07%, Capitalizing 34.84%, Grammatical Error (Usage) 2.52%, Sentence Pattern 4.04%, pronoun 49.49%, Spelling 2.02%. From the result, it can be concluded that the students should learn Grammar especially about pronoun, because of the mistakes that most students do.